Answer:
It'll take 25 hours to get to the auto shop
Step-by-step explanation:
Given
Distance = 5 miles
Speed =1056 feet per hour
Required
How long will it take to the auto shop
This can be solved using Speed's formula;
![Speed = \frac{Distance}{Time}](https://tex.z-dn.net/?f=Speed%20%3D%20%5Cfrac%7BDistance%7D%7BTime%7D)
Substitute values for Speed and Distance
![\frac{1056 ft}{hr} = \frac{5 miles}{Time}](https://tex.z-dn.net/?f=%5Cfrac%7B1056%20ft%7D%7Bhr%7D%20%3D%20%5Cfrac%7B5%20miles%7D%7BTime%7D)
1 mile = 5280 feet;
So:
![\frac{1056 ft}{hr} = \frac{5 * 5280 ft}{Time}](https://tex.z-dn.net/?f=%5Cfrac%7B1056%20ft%7D%7Bhr%7D%20%3D%20%5Cfrac%7B5%20%2A%205280%20ft%7D%7BTime%7D)
![\frac{1056 ft}{hr} = \frac{26400ft}{Time}](https://tex.z-dn.net/?f=%5Cfrac%7B1056%20ft%7D%7Bhr%7D%20%3D%20%5Cfrac%7B26400ft%7D%7BTime%7D)
Cross Multiply
![Time * 1056ft = 26400ft * hr](https://tex.z-dn.net/?f=Time%20%2A%201056ft%20%3D%2026400ft%20%2A%20hr)
Divide both sides by 1056ft
![Time * \frac{1056ft}{1056ft} = \frac{26400ft * hr}{1056ft}](https://tex.z-dn.net/?f=Time%20%2A%20%5Cfrac%7B1056ft%7D%7B1056ft%7D%20%3D%20%5Cfrac%7B26400ft%20%2A%20hr%7D%7B1056ft%7D)
![Time = \frac{26400ft * hr}{1056ft}](https://tex.z-dn.net/?f=Time%20%3D%20%5Cfrac%7B26400ft%20%2A%20hr%7D%7B1056ft%7D)
![Time = 25hr](https://tex.z-dn.net/?f=Time%20%3D%2025hr)
<em>Hence, it'll take 25 hours to get to the auto shop</em>
Answer:
show the
Step-by-step explanation:
show the whole pic
Maybe try
<span><span><span><span>f(x) = 7 − 3x
(a)
f(a)
Incorrect: Your answer is incorrect.
(b)
f(−a)
(c)
−f(a)
(d)
f(a + h)
(e)
f(a) + f(h)
(f)
f(a + h) − f(a)
h
, if h ≠ 0 </span>
(Scroll Down for Answer!)</span><span>OR get immediate PAID help on:</span></span><span>Answer by </span>stanbon(72140) (Show Source):You can put this solution on YOUR website!
<span>If a and h are real numbers, find the following values for the given function.
f(x) = 7 − 3x
(a)
f(a) = 7-3a
------------------------
(b)
f(−a) = 7-3(-a) = 7+3a
------------------------
(c)
−f(a) = -(7-3a) = 3a-7
------------------------
(d)
f(a + h) = 7 -3(a+h) = 7-3a-3h
------------------------
(e)
f(a) + f(h) = (7-3a)+(7-3h) = 14-3a-3h
------------------------
(f)
if h ≠ 0,
[f(a + h) − f(a)]/h = {[7-3a-3h]-[7-3a]}/h = [-3h]/h = -</span></span>
Answer:
The second step is Distributive Property and the third is Subtraction Property of Equality
Step-by-step explanation:
The 1/2 is being distributed in the second step making the 8x to 4x and the 6 to 3.
The third step involves the subtraction of "x" from the right hand side and the left hand side.